Secure learning-based MPC via garbled circuit - Tjell, Katrine; Schluter, Nils; Binfet, Philipp; Schulze Darup, Moritz (2021 60th IEEE Conference on Decision and Control (CDC))

Encrypted dynamic control with unlimited operating time via FIR filters - Schluter, Nils; Neuhaus, Matthias; Schulze Darup, Moritz (2021 European Control Conference (ECC))

Tailored neural networks for learning optimal value functions in MPC - Teichrib, Dieter; Schulze Darup, Moritz (2021 60th IEEE Conference on Decision and Control (CDC))

Encrypted Control for Networked Systems: An Illustrative Introduction and Current Challenges - Schulze Darup, Moritz; Alexandru, Andreea B.; Quevedo, Daniel E.; Pappas, George J. (IEEE Control Systems)
Keywords: Electrical and Electronic Engineering; Modeling and Simulation; Control and Systems Engineering; Electrical and Electronic Engineering; Modeling and Simulation; Control and Systems Engineering

Exact solution to a special class of nonlinear MPC problems - Schulze Darup, Moritz; Klädtke, Manuel; Mönnigmann, Martin (IFAC-PapersOnLine)
Keywords: Control and Systems Engineering

Teaching MPC: Which Way to the Promised Land? - Faulwasser, Timm; Lucia, Sergio; Schulze Darup, Moritz; Mönnigmann, Martin (IFAC-PapersOnLine)
Keywords: Control and Systems Engineering

On Closed-Loop Dynamics of ADMM-Based MPC - Schulze Darup, Moritz; Book, Gerrit (Recent Advances in Model Predictive Control)

Fast Hands-Off Control Using ADMM Real-Time Iterations - Schulze Darup, Moritz; Book, Gerrit; Quevedo, Daniel E.; Nagahara, Masaaki (IEEE Transactions on Automatic Control)
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

On the Stability of Linear Dynamic Controllers With Integer Coefficients - Schluter, Nils; Darup, Moritz Schulze (IEEE Transactions on Automatic Control)
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

Encrypted MPC based on ADMM real-time iterations - Darup, Moritz Schulze (IFAC-PapersOnLine)
Keywords: Control and Systems Engineering

Encrypted explicit MPC based on two-party computation and convex controller decomposition - Schluter, Nils; Schulze Darup, Moritz (2020 59th IEEE Conference on Decision and Control (CDC))

Encrypted Cloud-based Control using Secret Sharing with One-time Pads - Schulze Darup, Moritz; Jager, Tibor (2019 IEEE 58th Conference on Decision and Control (CDC))

Exact representation of piecewise affine functions via neural networks - Schulze Darup, Moritz (2020 European Control Conference (ECC))

Encrypted Cooperative Control Revisited - Alexandru, Andreea B.; Schulze Darup, Moritz; Pappas, George J. (2019 IEEE 58th Conference on Decision and Control (CDC))

Encrypted polynomial control based on tailored two‐party computation - Schulze Darup, Moritz (International Journal of Robust and Nonlinear Control)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Mechanical Engineering; Aerospace Engineering; Biomedical Engineering; General Chemical Engineering; Control and Systems Engineering

Encrypted Model Predictive Control in the Cloud - Schulze Darup, Moritz (Privacy in Dynamical Systems)

Towards real-time ADMM for linear MPC - Schulze Darup, Moritz; Book, Gerrit; Giselsson, Pontus (2019 18th European Control Conference (ECC))

Verschlüsselte Regelung in der Cloud – Stand der Technik und offene Probleme - Schulze Darup, Moritz (at - Automatisierungstechnik)
Zusammenfassung Zukünftige Regelungskonzepte werden verstärkt auf Cloud-Computing und verteiltes Rechnen setzen. In den resultierenden vernetzten Regelungssystemen werden sensible Daten über öffentliche Netzwerke kommuniziert und auf Plattformen Dritter verarbeitet. Verschlüsselte Regelungen zielen darauf ab, die Vertraulichkeit dieser Daten im gesamten Regelkreis zu sichern. Um dieses Ziel zu erreichen, werden klassische Regelungsalgorithmen so modifiziert, dass sie verschlüsselte Regeleingriffe basierend auf verschlüsselten Systemzuständen berechnen. Zum Einsatz kommen dabei homomorphe Verschlüsselungsverfahren, die einfache mathematische Operationen auf verschlüsselten Daten ermöglichen. Der Artikel erläutert die Implementierung verschlüsselter Regelungen anhand von drei wegweisenden Realisierungen in der Cloud.
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

Efficient computation of RPI sets for tube-based robust MPC - Schulze Darup, Moritz; Teichrib, Dieter (2019 18th European Control Conference (ECC))